Modeling Individual Specific Fish Length from Capture–Recapture Data using the von Bertalanffy Growth Curve. Issue 4 (11th October 2013) - Schofield, Matthew R.; Barker, Richard J.; Taylor, Peter
Summary We use Bayesian methods to explore fitting the von Bertalanffy length model to tag‐recapture data. We consider two popular parameterizations of the von Bertalanffy model. The first models the data relative to age at first capture; the second models in terms of length at first capture. Using data from a rainbow trout Oncorhynchus mykiss study we explore the relationship between the assumptions and resulting inference using posterior predictive checking, cross validation and a simulation study. We find that untestable hierarchical assumptions placed on the nuisance parameters in each model can influence the resulting inference about parameters of interest. Researchers should carefully consider these assumptions when modeling growth from tag‐recapture data.